Characterization of Primary Cilia in Normal Fallopian Tube Epithelium and Serous Tubal Intraepithelial Carcinoma. Issue 8 (October 2018) - Abdelhamed, Zakia A.; Ryan, Thomas A.; Fuller, Martin; Coulson-Gilmer, Camilla; Abdelmottaleb, Dina I.; Wang, Tian-Li; Kaun, Jen-Chun; Wang, Peiyi; Hutson, Richard; Wilkinson, Nafisa; Bell, Sandra M.; Johnson, Colin A.
Abstract : Objectives: The aim of this study was to investigate the distribution of primary cilia on secretory cells in normal fallopian tube (FT) and serous tubal intraepithelial carcinoma (STIC). Methods: Fallopian tube tissue samples were obtained from 4 females undergoing prophylactic hysterectomies and 6 patients diagnosed with STIC. A mogp -TAg transgenic mouse STIC sample was also compared with a wild-type mouse FT sample. Serous tubal intraepithelial carcinoma was identified by hematoxylin and eosin staining and confirmed by positive Ki-67 and p53 immunohistochemical staining of tissue sections. We assessed the relative distribution of primary cilia on secretory cells and motile cilia on multiple ciliated cells by immunofluorescence and immunohistochemical staining. Ciliary function was assessed by immunofluorescence staining of specific ciliary marker proteins and responsiveness to Sonic Hedgehog signaling. Results: Primary cilia are widespread on secretory cells in the ampulla, isthmus, and in particular, the fimbriae of human FT where they may appear to mediate ciliary-mediated Sonic Hedgehog signaling. A statistically significant reduction in the number of primary cilia on secretory cells was observed in human STIC samples compared with normal controls ( P < 0.0002, Student t test), supported by similar findings in a mouse STIC sample. Immunohistochemical staining for dynein axonemal heavy chain 5 discriminated multiple motile cilia from primary cilia in human FT. Conclusions: Primary cilia are widespread on secretory cells in the ampulla, isthmus, and in particular, the fimbriae of the human FT but are significantly reduced in both human and mouse STIC samples. Immunohistochemical staining for ciliary proteins may have clinical utility for early detection of STIC. Abstract : Supplemental digital content is available in the text.